SYNTHESIS, CHARACTERIZATION, AND BIOLOGICAL-ACTIVITY OF POLYANION-CIS-DIAMMINEPLATINUM(II) COMPLEXES AS ANTITUMOR AGENTS - HAN, MJ; CHO, TJ; PARK, SJ; SOHN, YS; LEE, CO; CHOI, SU (TECHNOMIC PUBL CO INC, 1992)
Polyanion-cis-diammineplatinum(II) complexes were synthesized by the reaction of cis-[Pt(NH3)2(OH2)2](NO3)2 With the polyanions containing vic-dicarboxylate ions along the polymer chain. The eleven polyanions used for this synthesis were the hydrolysis products of polymers obtained by radical alternating copolymerizations of maleic anhydride with dihydropyran derivatives. For example, poly[(tetrahydropyran-5,6-diyl)(1,2-dicarboxyethylene)] derivatives were synthesized, which contained substituents, such as hydroxy, methoxy, ethoxy, acetoxy, methoxycarbonyl and acetoxymethyl groups, on the 2, 3 and 4-positions of the tetrahydropyran ring. The complex formation of cis-diammineplatinum(II) with vic-dicarboxylate groups was confirmed by the absorption at 1350 cm-1 for gamma(s)(CO) coordinated with Pt(II). By changing the mole ratios of the reactants, the platinum content in the polyanion complexes can be controlled and every 5-15 repeating units of the polymers were found to contain one cis-diammineplatinum(II). The biological activity of the polyanion-Pt complexes as measured in vitro against A-549 nonsmall cell lung, SK-OV-3 ovarian, HCT-15 colon, XF-498 CNS and L1210 leukemia. After selecting active complexes, the increased life spans were measured against L1210 and found to be 244, 143 and 178% for the complexes (8), (13) and (16), respectively.